Innovation strategies and performance: Are they truly linked? - Abdullah, Haim Hilman; Kaliappen, Narentheren (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this paper is to test the linkage between innovation strategies (process innovation and service innovation) and organizational performance in the context of Malaysia hotel industry. Design/methodology/approach – A total of 475 sets of questionnaires administrated through mail to all three star and above rating hotel managers in Malaysia, and only 24 percent of it, which is 114 were usable. Regression was utilized to test the link of innovation strategies and performance. Findings – The results showed that hotels in Malaysia used process innovation and service innovation as their functional-level strategy. Specifically, both process innovation and service innovation strategies positively linked with performance. But, the paired sample t-test result indicated that process innovation has slightly greater effect on performance than service innovation.In addition, this study found that hotel size significantly affected the performance.Research limitations/implications – This study is one of the limited number of studies which has empirically addressed the effect of innovation strategies on performance in hotel industry.Additional researches are needed to address effect of potential mediators or even moderators in innovation strategies and performance linkage.Practical implications – This study found that implementation of process innovation and service innovation as their functional strategy could assist to attain better performance in Malaysia hotel industry. Entirely the findings provided new insight to the hotel management in understanding the role of innovation strategies in generating enhanced performance. Originality/value – Process innovation and service innovation in the service industry have received very limited empirical attention in current innovation literature. This study extended the body of knowledge in innovation literature, particularly in hospitality sector in Malaysia.